Sala de leitura nas escolas da rede municipal de ensino de São Paulo: uma inovação que resiste às descontinuidades políticas - Mendes, Mônica Fátima Valenzi (2006)
The subject of this research is the Reading Room Project of the public education network of the São Paulo city, which is analyzed as an innovation of space/time that resists to the political discontinuities suffered by the city administration. The investigation focuses on the relations between schools and culture. Guiding question relates to the process through which the Project is implemented, instituted and continued. The research took place during the years of 2003, 2004 and 2005 and aimed to contribute with the understanding of the school based on the changes that occurred in this project, identifying the reasons, circumstances and factors (both internal and external) of its development. Different sorts of documents were analyzed in the quest for answers. The investigation made possible the comparison between what was proposed for the Reading Rooms as described in the guidelines and records of collected documents, in the pertinent legislation and in the theoretical production of the various authors studied. In the analysis of results, anchored on the Sociology of Education and on the Sociology of Culture, the main theoretical interlocutors were Williams, Bourdieu, Chartier and Weber. Conclusions suggest that the Reading Room constitutes an innovation that has persisted over the last three decades of the 20th century despite the political discontinuities of several administrations. It was detected a constant movement with determinations that there are tensions and conflicts, real changes in the school and in the administrations, and in the configuration of a new teacher created for the specific functions of the Reading Room. It was possible to detect the facets of culture in which aspects of reproduction are uncovered, in addition to new meanings presented and tested, making up the production of culture in its creative nature.